Healthcare musicians and musico-emotional work : An in-depth case study within the context of end-of-life care - Koivisto, Taru-Anneli (Greek Association of Primary Music Education Teachers, 2022)
The purpose of this in-depth case study is to explore the work of musicians in end-of-life care. In this study, a healthcare musician is considered to be a professional who has both an academic degree in music and in-service training in music and healthcare settings. In addition to working with healthcare personnel, they often collaborate with music therapists to provide integrated healthcare services for the best patient care. In the study, six musicians who had experience in end-of-life care settings were interviewed. Their reflections on their socially engaged work were analysed through the emerging theoretical lens of emotional work. This resulted in the identification of three themes beyond that of pure performativity in music professionalism, relating to the emotional work in end-of-life care. Furthermore, the emotional processes that were encountered, which were deeply social in nature, were conceptualised as musico emotional work. This other-centred work aligns with music therapy research, and is an essential part of music therapists’ end-of-life work. In conclusion, the similarities between music therapists and musicians, as well as the interprofessional potential of their cooperation, are reflected upon.
Keywords: musiikkiterapia; muusikot; terveydenhuolto